Durability of flexurally strengthened RC beams with prestressed CFRP sheet under wet–dry cycling in a chloride-containing environment. (1st January 2021) - Lu, Zhongyu; Li, Jianglin; Xie, Jianhe; Huang, Peiyan; Xue, Lingfeng
Abstract: Using prestressed carbon fibre reinforced polymer (CFRP) to strengthen reinforced concrete (RC) members is currently considered a promising technology. This study aims to investigate the durability of RC beams externally strengthened with prestressed CFRP sheet in a chloride-containing environment. The prestressed load levels were set at 7.5%, and 15% of the ultimate tensile strength of the CFRP sheet at room temperature (~26 °C), and the test parameters included an inclined U-jacket (or not) and 90-day exposure to a wet–dry cyclic environment. The wet–dry cyclic condition was set as 8-h immersion in 3.5% NaCl solution at 40 °C and 16-h drying at 25 °C and 60% RH (relative humidity). After exposure to the wet–dry environment, the prestressed CFRP sheet strengthened RC beams were tested under four-point bending test. The evolution of time-dependent prestress losses in the strengthened beam was discussed, and then the flexural behaviour of the strengthened beams was analyzed. Finally, a theoretical model based on the classical beam theory was proposed to predict the bearing capacity of prestressed-CFRP strengthened RC beams. The results show that the prestressed CFRP sheet can significantly improve the flexural performance of RC beams, and the cracking and ultimate loads of the RC beam strengthened with a prestressing level of 15% could increase by approximately 50% and 40%, respectively. Moreover, the inclined U-jacket enhanced the flexural performance of the strengthened RC beams and changed the failure mode from CFRP debonding to CFRP fracture. Although the exposure in chloride-containing environments increased the prestress losses, a 90-day exposure in the simulated subtropical marine climate environment did not cause a significant detrimental influence on the flexural performance of the strengthened RC beams. The proposed model agrees well with the experimental results, indicating it could conservatively predict the bearing capacity of strengthened RC beams failed by CFRP fracture.